Pemberian Suplemen Makanan Fituno Kimia Farma dalam Membantu Menjaga Daya Tahan Tubuh Bagi Sumber Daya Manusia (SDM) Fakultas Kedokteran dan Ilmu Kesehatan Universitas Pertahanan RI - Pujowaskito, Prihati; Ibrizatun, Amin; T.W, Lila Irawati; Yochanan, E.; Rahman, Arief; Pannyiwi, Rahmat (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Indonesia has a big challenge to face currently, namely health problems. Three important health problems include the increase in non-communicable diseases, infectious diseases and the emergence of diseases that should have been successfully overcome. One model for maintaining health problems and/or a healthy immune system is by adopting a nutritious food and drink pattern. There are several foods and drinks that can strengthen the immune system, one of which contains Echinaceae, Morindae, Pylarthi, Vitamin B1 HCL, Vitamin B6 HCL, Vitamin E. Therefore, it is very important to consume Kimia Farma's Fituno Food Supplement to help maintain the body's immune system regularly. As an effort to increase endurance for Human Resources of the Faculty of Medicine and Health Sciences, Defense University of the Republic of Indonesia in carrying out daily activities. The implementation method used in this activity includes providing Fituno Kimia Farma Food Supplements. The results of this activity are related to efforts to increase body endurance through regular consumption of Fituno Kimia Farma Food Supplement products in collaboration with the Faculty of Medicine and Health Sciences through the Dean, Dr. Dr. Prihati Pujowaskito, Sp.JP (K)., FIHA., M.M.R.S. Our hope for the future is that the Fituno Kimia Farma Food Supplement will continue to meet the human resource needs of the Faculty of Medicine and Health Sciences, Defense University of the Republic of Indonesia.